Pengembangan Soal Higher Order Thinking Skills (HOTS) Pada Materi Sumpah Pemuda Dan Jati Diri Keindonesiaan di SMA Pembangunan Laboratorium Universitas Negeri Padang - Nofrialdi Oscar; Ofianto Ofianto (Jurnal Kronologi, 2019)
The problem in this research is thinking ability Higher Order Thinking Skills (Hots) of students who are still low on history subjects. It can be seen from the learning outcomes of students that are still low.Therefore, the researcher wants to develop the matter of history on the learning material "Sumpah Pemuda dan Jati Diri Keindonesiaan" in Senior High School of Pembangunan Laboratorium Padang State University. This type of research is Research and Development. The development design used is a formative research design guided by Tessmer, which is divided into four stages: preliminary, self-evaluation, prototyping and field test. The subjects used were students of class XI Senior High School of Pembangunan Laboratorium Padang State University. Data was collected by conducting a series of tests on the subject in the form of test and validation instrument sheets. Data collection techniques used are tests. The instruments used in this research are test instruments and validation sheets. The accuracy of the validator's assessment on the validation blank is correct or not based on content (curriculum and material), constructs (characteristics/ HOTS indicators), and language (in accordance with applicable rules/ EYD). From the results of the study it was found that the test instrument used was in accordance with the criteria at the prototype and field stages. Va value generated is 4.13 with the category "Valid" on the instrument. The instrument is known to be reliable 0.786 with a "high" classification. Each question is feasible to use with the difficulty level "Medium" and "Easy" and there is no distinguishing power of "Very Bad". The test instrument produced was classified as good with 11 items.